Status gizi siswa sekolah dasar sebelum program makan bergizi gratis di SD Negeri Inpres Skouw Sae Kota Jayapura - Nur, Syaharuddin; Irmanto, Maxsi; Fatiah, Mona Safitri (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: The nutritional status of elementary school children is an important indicator of health and human resource capacity. Baseline data are needed prior to the implementation of the Free Nutritious Meal Program (MBG), particularly in border areas facing limited food access, logistical distribution challenges, and socio-economic disparities compared to urban regions. Such data are also relevant to support national policies on stunting reduction and the MBG program as a government strategy to improve child nutrition.Objectives: To describe the nutritional status of students at SD Negeri Skouw Sae and analyze its association with sex, age, ethnicity, recent illness, and parental occupation, while providing baseline data for evaluating the effectiveness of the MBG program in border areas.Methods: A cross-sectional study was conducted among 121 active students. Inclusion criteria were all actively enrolled students, while exclusion criteria included children with chronic diseases that might affect anthropometric measurements. Nutritional status was assessed using Body Mass Index-for-Age (BMI-for-Age) based on WHO 2007 standards. This indicator was chosen because it is practical for school-based surveillance, reliable for assessing school-age children’s nutrition, and internationally recommended as a primary parameter for nutrition monitoring. Data were analyzed using the Chi-square test with a significance level of α=0,05 in SPSS version 22.Results: Most students (89,3%) had good nutritional status, while 10,7% were classified as undernourished. Bivariate analysis with the Chi-square test did not reveal significant associations between nutritional status and sex, age, ethnicity, parental occupation, or recent illness. These findings are descriptive and should be interpreted with caution, as the analysis did not control for covariates.Conclusion: The majority of students at SD Negeri Skouw Sae had good nutritional status (89,3%) prior to the implementation of the MBG program. No significant associations were found between nutritional status and demographic factors (sex, age, ethnicity, parental occupation) or short-term health factors (recent illness). These descriptive findings provide important baseline data for monitoring and evaluating the effectiveness of the MBG program in border areas of Papua and highlight the need for further studies considering dietary intake and school environment factors.